1988
DOI: 10.1212/wnl.38.6.886
|View full text |Cite
|
Sign up to set email alerts
|

Sensory motor neuropathy associated with AIDS

Abstract: Clinical, laboratory, and pathologic observations in six patients with sensory motor peripheral neuropathy associated with the acquired immunodeficiency syndrome (AIDS) are presented. Blood and urine testing failed to reveal other causes for peripheral neuropathy. Distinctive CSF findings included elevated human immunodeficiency virus-specific indices. Peripheral nerve pathology confirmed the results of electrodiagnostic studies and revealed axonal loss and demyelination. Epineurial and endoneurial mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…These authors were unable to detect deposition of immunoglobulin, complement, or fibrin by direct immunofluorescence. Several investigators have observed associated demyelination (Bailey et al, 1988;De la Monte et al, 1988), but this does not appear to be macrophage-mediated or segmental (Bailey et al, 1988;Mah et al, 1988). In a study comparing autopsy specimens of HIV patients and controls, Bradley and colleagues (1998) found prominent axonal degeneration, segmental demyelination (5% to 6% of nerve fibers), T-cell and macrophage infiltration, and cytokine expression.…”
Section: Laboratory Featuresmentioning
confidence: 99%
“…These authors were unable to detect deposition of immunoglobulin, complement, or fibrin by direct immunofluorescence. Several investigators have observed associated demyelination (Bailey et al, 1988;De la Monte et al, 1988), but this does not appear to be macrophage-mediated or segmental (Bailey et al, 1988;Mah et al, 1988). In a study comparing autopsy specimens of HIV patients and controls, Bradley and colleagues (1998) found prominent axonal degeneration, segmental demyelination (5% to 6% of nerve fibers), T-cell and macrophage infiltration, and cytokine expression.…”
Section: Laboratory Featuresmentioning
confidence: 99%
“…When present they are usually perivascular, range from minimal to very prominent, and do not correlate with the clinical severity, or even presence, of the neuropathy (Bailey et al 1988 ;Chaunu et al 1989 ;de la Monte et al 1988 ;Fuller et al 1993 ;Kiprov et al 1988 ;Gastaut et al 1989 ;Vital et al 1992 ;Winer et al 1992 ). Absence of infl ammation may be related to systemic depletion of lymphocytes, as DSPN during AIDS-related complex (ARC) is more likely to show lymphocytic infi ltration than DSPN during AIDS (Chaunu et al 1989 ;Leger et al 1988 ).…”
Section: Light Microscopymentioning
confidence: 99%
“…11.5 ), with less prominent segmental demyelination (Gastaut et al 1989 ;Kiprov et al 1988 ;Winer et al 1992 ;Bailey et al 1988 ;Vital et al 1992 ). Large myelinated fi bers may be more involved (Gastaut et al 1989 ), although this could refl ect axonal atrophy rather than true selective loss of large axons (Fuller et al 1990a ).…”
Section: Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV particles are found in the vessel walls, Schwann cells, and perivascular macrophages. This could point to direct or indirect invasion by HIV [7,8].…”
Section: Introductionmentioning
confidence: 99%